Mental training as a strategy to improve self-confidence in extracurricular volleyball athletes - Marcela Puput Devita; Eka Darisman; Mulyono Mulyono; Gatot Margisal Utomo (Universitas Sriwijaya, 2026)
Research Background: Self-confidence is a crucial psychological factor influencing athletic performance. However, many school-aged athletes with adequate technical skills are still unable to perform optimally during competition due to low self-confidence. Research Objective: This study aimed to analyze the effect of mental training on improving the self-confidence of volleyball athletes participating in the extracurricular program at SMA Al Islam Krian. Methods: A quantitative approach with a one-group pretest–posttest design was employed involving 20 volleyball athletes. The intervention consisted of a four-week mental training program conducted twice a week, including positive imagery, positive self-talk, and controlled breathing techniques. Data were collected using a self-confidence questionnaire and analyzed through descriptive statistics and a paired-samples t-test. Results: The mean self-confidence score increased significantly from 12.25 at pretest to 24.50 at posttest (p < .05). Conclusion: Mental training was effective in enhancing the self-confidence of volleyball athletes and is recommended for integration into school-based athlete development programs.